(untitled) (Zoological Records and Reviews, 2025)
Molecular tools have transformed zoology from a discipline dependent on morphological observation and field survey to one capable of resolving population structure, species boundaries, dietary ecology, pathogen dynamics, and landscape connectivity from minute biological samples or environmental residues. This review synthesises the applications and impacts of six major molecular tool categories – DNA barcoding, environmental DNA (eDNA), next-generation sequencing (NGS) including metabarcoding, population genomics, stable isotope analysis, and quantitative PCR – across five zoological application domains: species identification and discovery, population genetics and connectivity, dietary and trophic ecology, disease surveillance, and non-invasive individual identification. Drawing on 248 primary studies published between 2010 and 2024 and a quantitative assessment of methodological performance metrics, we demonstrate that molecular approaches have expanded zoological detection sensitivity by 2-8-fold for rare and cryptic species relative to traditional survey methods, resolved previously intractable population connectivity questions for wide-ranging and migratory species, and enabled real-time disease surveillance in wildlife populations. eDNA metabarcoding now detects 38-84% more aquatic taxa per sampling event than morphological identification of equivalent kick-net samples. Population genomics (SNP arrays, whole-genome resequencing) has replaced microsatellite-based population genetics as the standard for conservation genetics in the past five years, providing 100-10,000-fold greater marker resolution with decreasing costs. Key methodological challenges – standardisation, contamination management, and computational bottlenecks – are identified alongside emerging solutions. These findings establish molecular tools as indispensable infrastructure for 21st-century zoological research and biodiversity monitoring under the Kunming-Montreal GBF Target 21 (biodiversity knowledge base) framework.